Devices for balneotherapy in Polish spa in XIX century (In the Mirror of Things, 2022)
In the nineteenth century, there was a renaissance in the use of water in medicine, a method that was already used in antiquity, but also a rapid boom in various types of treatments with the use of water, including mineral ones. Vincenz Priessnitz (1799–1851) and priest Sebastian Kneipp (1821–1897), who founded a hydrotherapy facility in Bad Wörishofen, contributed primarily to the development of hydrotherapy in 19th century Europe. It was this town that was modeled on by other hydrotherapy supporters in the 19th century, establishing their own natural medicine facilities. Various devices and accessories were used during these treatments. Along with the rapid development of hydrotherapy, the equipment used in this water therapy was modernized, in which, however, the most important thing was the bathtub. The aim of the article is to show this evolutionary process on the example of selected Polish spa towns (in Galicia and the Kingdom of Poland) where hydrotherapeutic treatments were used throughout the long 19th century. The reflections were based on the analysis of information sources and brochures issued by health resorts as well as texts published in the press at that time. Iconographic material also played an important role.